Cytomegalovirus infection in infants with biliary atresia in China: a multi-center investigation study - Zhao, Yilin; Xu, Xiaodan; Meng, Yu; Zhou, Chonggao; Zheng, Baijun; Zhang, Xianwei; Wang, Bin; Duan, Xufei; Liu, Yuanmei; Feng, Jiexiong; Zhu, Jie; Zhang, Zhibo; et al. (Frontiers in Pediatrics, 2025)
Background and objectivesBiliary atresia (BA) with concurrent cytomegalovirus (CMV) is a distinct subtype that is linked to a poorer prognosis. Currently, there are no standardized criteria for the diagnosis or antiviral treatment (AVT) of this condition. It has a high prevalence in China. The aim was to investigate the infection, diagnosis and treatment of CMV infection in infants with BA through a multicenter questionnaire survey conducted in China.MethodsA multicenter investigation was performed through online questionnaire survey. It investigated the diagnosis and treatment of infants with CMV-infected BA in tertiary-level pediatric centers from January 1st, 2018, to January 1st, 2020. The centers were categorized into low and high-volume groups based on number of infants with BA (≤50 or >50) and were also grouped geographically into south and north groups. Afterward, 100 cases were randomly selected from these infants for a retrospective analysis.ResultsA total of 22 questionnaires were collected, and 20 were included in the analysis. The questionnaire survey encompassed 1,276 infants with type III BA. 31.3% of the infants of BA had CMV detected. According to the survey results, a large proportion of centers preferred using CMV-DNA (75.0%) and CMV-IgM (95.0%) as their preferred methods for CMV detection. In the high-volume group, more centers opted for CMV-DNA detection (100.0% vs. 66.7%) and administered AVT (87.5%). In the retrospective analysis of 100 infants with BA, 39 were found to be CMV-positive and among these, 74.4% received AVT.ConclusionAmong the 1,276 infants with BA in this cohort, 31.3% (399 cases) had concomitant CMV infection, representing a decrease compared to previous data. CMV-IgM played a crucial role in the detection of the infection. The retrospective analysis indicated that AVT had a beneficial impact on the prognosis of infants with BA who were infected with CMV.